Costs and Returns for Sugarcane Production on Muck Soils in Southern Florida 2008–2009 - Fritz M. Roka; Leslie E. Baucum; José Alvarez (EDIS)
SC088, a 14-page report by Fritz M. Roka, Leslie E. Baucum, and José Alvarez, estimates an enterprise budget that reflects annual costs and returns for a 5,000-acre farm that grows sugarcane on organic soil, commonly referred to as “muck.” Includes references. Published by the UF Department of Food and Resource Economics, March 2010.